"There's only three things he mentions in a sentence – a noun, a verb and 9/11": terrorism, fear and the after, after 9/11. Issue 1 (2nd January 2019) - Stohl, Michael
ABSTRACT: In the years since 11 September 2001, pundits, politicians and scholars of terrorism and international relations routinely have declared that 9/11 "changed everything". This article explores not only how those decisions transformed the United States and the global response to terrorism, but also how both the decisions and response sustained a sense of fear. Further, they made possible, to paraphrase then candidate Joseph Biden's critique of former New York Mayor Rudy Guiliani, the framing of so much of the global political debate about terrorism, and national security references as simply 9/11 accompanied by a noun and a verb. Finally, the article examines the consequences of this framing for not only our understanding of terrorism, but also our understanding of terrorism and violence within the current global system.